Identifying Subgroups of Care Providers Participating in a Telehealth Educational Intervention: Hierarchical Cluster Analysis of Evaluation Data. (January 2015) - Wao, Hesborn; Beckstead, Jason W.; Beal, Jeffrey; Aluoch, Marilyn; Skipper, Theresa C.; Orrick, Joanne J.
Health care providers (HCPs) serving HIV-infected patients, especially in rural and underserved areas, have limited access to continuing medical education. Objective: To identify subgroups of HCPs who might benefit from a telehealth training program focusing on HIV/AIDS care based on HCPs' objective for attending the training. Methods: Hierarchical cluster analysis combined with thematic analysis identified the subgroups. Results: A total of 56 HCPs attended between 1 and 9 of the 12 sessions conducted (mean ≈ 2, standard deviation = 1.6). Subgroups identified included knowledge (HCPs interested in gaining, increasing, or updating their knowledge in HIV care), learn–expert (HCPs interested in learning, obtaining, or providing expert opinion), and observe–apply–network (HCPs interested in observing the training, applying knowledge gained to practice, and networking). No group differences were found in the participants' reaction to the session, change in knowledge following the training, and other important characteristics. Conclusion: Methodological contributions of the study are discussed.